Pembentukan Karakter Peduli Sosial Melaui Pembelajaran IPS - Isnaeni, Yuni; Ningsih, Tutuk (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to determine some of the methods of teachers in an effort to form a character of social care in the learning environment at school and the environment where students live. The method used in this research is descriptive qualitative, namely describing or describing the situation at MI P2A Meri about the learning carried out by the teacher in shaping the character of social care through social studies learning. The population used was grade 4 students of MI Meri totaling 30 students and the sample taken for research based on the Slovin formula was 28 students. The instrument used in this study was the research guideline grid with P2A as an indicator of the character of social care. The research results obtained in the formation of social care character of MI P2A Meri through integration of subjects and integration of school culture. Integrase subjects by including character values, help each other, like to share with others on lesson plans. Making student inspirational figures so that students become stronger in social care. The integrity of the school culture that is carried out is to provide service facilities in social activities, including 1) sharing food with friends, 2) thanking school cleaners, 3) lending stationery to friends who do not, bring or do not have one. 4) collect money and goods for victims of natural disasters, 5) visit homes for orphans and the elderly, 6) respect school officials. 7) help a friend who is in need of help. 8) donate blood. By participating in the learning and school culture program, students will get used to social care for their respective students